Jeremiah 17:11 and blood money rituals among youths in southern Nigeria - Uroko, Favour C. (Theologia Viatorum (Sorenga), 2022)
This study examines blood money ritual activities among Nigerian youths in the light of Jeremiah 17:11. Existing literature has failed to provide a response through a theological lens to blood money ritual activities in southern Nigeria. This study provides a theological response to the increasing spate of money ritual activities among southern Nigerian youths. The pericope of Jeremiah 17 explains the repercussions of the man who accumulates wealth by fraud and treachery. The pericope emphasises that this form of wealth will finally be taken away from him and he may die a fool. This aphorism suits the contemporary blood money ritual activities occurring in southern Nigeria. The number of money ritual activities in southern Nigeria is mind-blowing and thought-provoking. There is hardly a week that passes without the youth’s engagement in blood money rituals coming up for discussion. From the reports of newspapers and other reports, poverty, unemployment, greed and peer pressure are some of the motivating factors for youth engaging in blood money ritual activities. This study adopted the phenomenological approach through content analysis of reports from gazettes and scientific journals.Contribution: Jeremiah 17:11 reveals that there is punishment for anyone who makes wealth through dishonest ways. This study found that greed has sustained the increasing quest for quick money among youth in Nigeria. Practical theology was implicated in this study.